Answer :

LHS


We know that





We know that a3 + b3 = (a + b) (a2 + b2- ab)




= 1 – (sin2x + cos2x) + sinx cosx


We know that sin2x + cos2x = 1.


= 1 – 1 + sinx cosx


= sinx cosx


= RHS


Hence proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

True and False<brMathematics - Exemplar

Find the values oRD Sharma - Mathematics

Prove that :
<
RD Sharma - Mathematics

The value of cos<Mathematics - Exemplar

The value of sin Mathematics - Exemplar

cos 2θ cos 2<spanMathematics - Exemplar

The value of <spaMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

Fill in the blankMathematics - Exemplar